Mediating effect of risk propensity between impulsivity and psychotic experiences among Lebanese young adults - Lea Kanbar; Diana Malaeb; Fouad Sakr; Mariam Dabbous; Feten Fekih-Romdhane; Souheil Hallit; Sahar Obeid (Discover Mental Health)
Abstract Background Psychotic experiences pose a significant public health concern among young adults. These subclinical symptoms can disrupt daily functioning and are often linked to risk propensity. Impulsivity, a multidimensional construct involving traits such as sensation seeking and lack of premeditation, has been implicated in various psychopathologies, including psychotic disorders. This study investigates the mediating role of risk propensity in the relationship between impulsivity and psychotic experiences among Lebanese young adults. Methods It was a cross-sectional study conducted with 433 participants recruited through a snowball sampling technique. The following scales have been used: General Risk Propensity scale (GRiPS), Prodromal Questionnaire-Brief scale (PQ-B), and Impulsive Behavior Short Scale-8 (I-8). Results The results of this mediation analysis revealed that risk propensity fully mediated the relationship between impulsivity and psychotic experiences (indirect effect: Beta = 0.08, Boot SE = 0.02; 95% CI 0.04; 0.11). Higher impulsivity was significantly associated with increased engagement in risk propensity, which, in turn, was significantly associated with greater severity of psychotic experiences. Direct association between impulsivity and psychotic experiences was not significant. Conclusion These findings highlight the pivotal role of risk propensity in the link between impulsivity and psychotic experiences among Lebanese adults. Future research should explore longitudinal designs to establish causality and investigate intervention strategies aimed at reducing risk propensity to mitigate the impact of impulsivity on psychotic symptoms.